Responsibility for Currency in an Occupied Territory - Skubiszewski, Krzysztof (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The paper is an English translation of the chapter Odpowiedzialność za pieniądz na terytorium okupowanym from Pieniądz na terytorium okupowanym. Studium prawnomiędzynarodowe ze szczególnym uwzględnieniem praktyki niemieckiej by Krzysztof Skubiszewski published originally in Polish by Instytut Zachodni Publishing House in 1960. The text is published as a part of a jubilee edition of the Adam Mickiewicz University Law Review “100th Anniversary of the Faculty of Law and Administration” devoted to the achievements of the late Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.